A Review of the Pathophysiology and Treatment of Psychosis in Parkinson’s Disease - Zahodne, Laura B. (2008)
Psychotic symptoms in Parkinson’s disease (PD) are relatively common, and in addition to being a disturbance to patients’ daily lives, they have consistently been shown to be associated with poor outcome. Our understanding of the pathophysiology of psychosis in PD has expanded dramatically over the past fifteen years, from an initial interpretation of symptoms as dopaminergic drug side effects to the current view of a complex interplay of extrinsic and disease-related factors. The present article reviews the unique clinical features of psychosis as expressed in PD, associated risk factors, and current theories behind its pathogenesis, including medications, visual processing deficits, sleep disturbances, genetics, and neurochemical and structural abnormalities. Finally, we review both traditional and emergent management strategies for PD psychosis, including antipsychotic agents, cholinesterase inhibitors, electroconvulsive therapy (ECT), and other pharmacological and psychological interventions.